Once and Always - McNaught, Judith (London Corgi Books, 1997)
Across the vast ocean sailed Victoria Seaton, a free-spirited American beauty left suddenly orphaned and alone. Eager to claim her long-lost heritage, she was amazed at the formal elegance of Wakefield, the sumptuous English estate of her distant cousin ... the notorious Lord Jason Fielding. Sought after at plays, operas, and balls by London's most fashionable ladies, Jason remained a mystery to Victoria. Bewildered by his arrogant demeanor, yet drawn to his panther-like grace, she came to sense the searingly painful memories that smoldered in the depths of his jade-green eyes.
Keywords: English fiction